Direct Transcatheter Heart Valve Implantation Versus Implantation With Balloon Predilatation: Insights From the Brazilian Transcatheter Aortic Valve Replacement Registry. (August 2016) - Bernardi, Fernando L.M.; Ribeiro, Henrique B.; Carvalho, Luiz A.; Sarmento-Leite, Rogerio; Mangione, José A.; Lemos, Pedro A.; Abizaid, Alexandre; Grube, Eberhard; Rodés-Cabau, Josep; de Brito, Fábio S.
Abstract : Background—: Direct transcatheter aortic valve replacement (TAVR) is regarded as having potential advantages over TAVR with balloon aortic valve predilatation (BAVP) in reducing procedural complications, but there are few data to support this approach. Methods and Results—: Patients included in the Brazilian TAVR registry with CoreValve and Sapien-XT prosthesis were compared according to the implantation technique, with or without BAVP. Clinical and echocardiographic data were analyzed in overall population and after propensity score matching. A total of 761 consecutive patients (BAVP=372; direct-TAVR=389) were included. Direct-TAVR was possible in 99% of patients, whereas device success was similar between groups (BAVP=81.2% versus direct-TAVR=78.1%; P =0.3). No differences in clinical outcomes at 30 days and 1 year were observed, including all-cause mortality (7.6% versus 10%; P =0.25 and 18.1% versus 24.5%; P =0.07, respectively) and stroke (2.8% versus 3.8%; P =0.85 and 5.5% versus 6.8%; P =0.56, respectively). Nonetheless, TAVR with BAVP was associated with a higher rate of new onset persistent left bundle branch block with the CoreValve (47.7% versus 35.1%; P =0.01 at 1 year). Mean gradient and incidence of moderate/severe aortic regurgitation were similar in both groups at 1 year (11% versus 13.3%; P =0.57 and 9.8±5.5 versus 8.7±4.3; P =0.09, respectively). After propensity score matching analysis, all-cause mortality and stroke remained similar. By multivariable analysis, BAVP and the use of CoreValve were independent predictors of new onset persistent left bundle branch block. Conclusions—: The 2 TAVR strategies, with or without BAVP, provided similar clinical and echocardiographic outcomes over a midterm follow-up although BAVP was associated with a higher rate of new onset persistent left bundle branch block, particularly in patients receiving a CoreValve. Abstract : Supplemental Digital Content is available in the text.